2007
DOI: 10.1590/s0100-40422007000200005
|View full text |Cite
|
Sign up to set email alerts
|

Teores de corantes artificiais em alimentos determinados por cromatografia líquida de alta eficiência

Abstract: Recebido em 14/7/05; aceito em 25/5/06; publicado na web em 26/9/06 CONTENTS OF SYNTHETIC DYES IN FOODS DETERMINED BY HIGH PERFORMENCE LIQUID CHROMATOGRAPHY. Synthetic dyes are much used in processed foods. HPLC was applied to different types of snacks, such as colored cereals, chocolate confetti, chewing gums and candies for the determination of those additives. In the case of artificially colored breakfast cereals, 71% of the samples exceeded the allowed limits. Regarding the portions recommended for consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
19

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 4 publications
(8 reference statements)
0
8
1
19
Order By: Relevance
“…In two samples of chocolate confectionery four dyes were found. 20 Also in our study it was observed that the solid preparations for Refreshment of that brand were four dyes, being in disagreement with the Brazilian legislation which allows the use in maximum of three dyes. 21 The presence of dyes above recommended by Brazilian legislation of ultra-processed industrialized products samples demonstrates consumer vulnerability, because the higher the amount of dye in the product, the greater the risk of adverse health effects.…”
Section: Resultscontrasting
confidence: 54%
“…In two samples of chocolate confectionery four dyes were found. 20 Also in our study it was observed that the solid preparations for Refreshment of that brand were four dyes, being in disagreement with the Brazilian legislation which allows the use in maximum of three dyes. 21 The presence of dyes above recommended by Brazilian legislation of ultra-processed industrialized products samples demonstrates consumer vulnerability, because the higher the amount of dye in the product, the greater the risk of adverse health effects.…”
Section: Resultscontrasting
confidence: 54%
“…Além disso, os corantes identificados nesses doces pertencem ao grupo Azo, um derivado nitroso reconhecido como uma substância capaz de causar reações alérgicas como asma e urticária, e tem sido alvo de estudos de mutagênese e carcinogênese por produzir amina aromática, e ácido sulfanílico após ser metabolizado pela microflora intestinal. São também denominados compostos azóicos, azoderivados ou azocompostos 16,17 .…”
Section: Metodologiaunclassified
“…Foram encontrados os corantes: amaranto (37%), amarelo crepúscu-lo (33%) e tartrazina (28%), respectivamente. O amaranto esteve presente em 50% das amostras do xarope de groselha em concentração acima do teor permitido pela legislação, caracterizando fraude 16,17 . Os autores alertaram para o fato da quantificação do teor de corante ter sido realizada na amostra diluída como indicado no rótulo, porém, alguns consumidores, principalmente as crianças, fazem uso desse produto muitas vezes na forma concentrada, como em coberturas para sorvetes e bolos 18 .…”
Section: Metodologiaunclassified
“…Os autores realizaram testes de recuperação mediante metodologias de diversos pesquisadores tendo obtido resultados diferentes porém aceitáveis dada a pequena variabilidade encontrada, e levantam a hipótese que a baixa incidência de patulina possa estar relacionada à sulfitagem dos sucos comerciais, permitido pela legislação brasileira, mas nada foi feito para confirmação. Utilizando a mesma metodologia para detecção da toxina, Prado et al (2000) verificaram a incidência de patulina em 13 amostras de suco de maçã comercializadas em Belo Horizonte, Minas Gerais-Brasil, e encontraram níveis detectáveis (10 μg/L) de patulina em apenas uma das amostras.…”
Section: Dombrink-kurtzman E Blackburnunclassified
“…Com o aumento da produção nacional, aumentaram as exportações da fruta in natura e a venda para as fábricas de suco (WOSIACKI et al, 2002). A maior parte da produção nacional de suco concentrado de maçã destina-se à exportação, apresentando grande concorrência com a Argentina e Chile, países com tradição no processamento de maçãs e grandes produtores mundiais (PRADO, 2000).…”
Section: Introductionunclassified